Sobre três processos educativos em educação matemática para empreendimentos em economia solidária - Meneghetti, Renata Cristina Geromel; Shinkawa, Geisa Zilli; Azevedo, Michelle Francisco de [UNESP]; Kucinskas, Ricardo (My University, 2013)
This paper focuses on Mathematics Education in the context of Solidarity Economy and aims to approach our performance, aiming to answer demands of Mathematics Education of the three Solidarity Economy Enterprises (SEE): a cooperative cleaning, of a women carpenter’s group and a group manufacturing homemade soap. Based on the Ethnomathematics, a pedagogical intervention with these SEE was performed, in which we attempted to work the Mathematics within the cultural context of these enterprises through problem situations related to their daily work and through non-formal education. The research followed a qualitative research and was characterized as action research. As a result we found that the approach applied has contributed to changes some attitudes of the research subjects, it was favorable to the learning of concepts and also the socioeconomic reintegration, in the direction of a posture more critical and emancipatory. Also, realize that non-formal education can indeed contribute to the ideals of Education in the Solidarity Economy as a way include those who have been socially excluded by formal education provided by the school.

Este trabajo se centra en la Educación Matemática en el contexto del Economía Solidaria y busca atender a nuestro desempeño, con el objetivo de satisfacer las demandas específicas de la Educación Matemática, con tres Emprendimientos de Economía Solidaria (EES): una limpieza cooperativa, una colectiva femenina carpintería y un grupo fabricación de jabón casero. Sobre la base de la etnomatemática, una intervención pedagógica junto a estos EES se llevó a cabo, en la que intentamos trabajar las matemáticas en el contexto cultural de estos EES, a través de situaciones problemáticas relacionadas con su trabajo diario y por medio de la educación no formal. La investigación siguió una investigación cualitativa y se caracterizó como la investigación-acción. Los resultados obtenidos indican que el enfoque aplicado ha contribuido a los cambios en las actitudes de los sujetos de la investigación, tanto favorables al aprendizaje de conceptos, como la reintegración socioeconómica, hacia una más crítica y emancipadora. Además, nos damos cuenta de que la educación no formal, en realidad, puede contribuir a los ideales de la Educación y de la Economía Solidaria como una manera de insertar socialmente aquellos que fueron excluidos por la educación formal proporcionada por la escuela.

Este trabalho focaliza a Educação Matemática no contexto da Economia Solidária e tem por finalidade abordar nossa atuação, visando atender a demandas específicas da Educação Matemática junto a três Empreendimentos em Economia Solidária (EES): uma cooperativa de limpeza, uma marcenaria coletiva feminina e um grupo de fabricação de sabão caseiro. Com base na etnomatemática, uma intervenção pedagógica junto a esses EES foi realizada, na qual buscou-se trabalhar a matemática no contexto cultural desses EES, por meio de situaçõesproblema relacionadas a seus cotidianos de trabalho e através da educação não formal. A pesquisa seguiu uma abordagem qualitativa de investigação e se caracterizou como pesquisaação. Como resultado, observamos que a abordagem aplicada contribuiu com mudanças de atitudes dos sujeitos da pesquisa, favoráveis tanto ao aprendizado dos conceitos, quanto à reinserção socioeconômica, em direção a uma postura mais crítica e emancipatória. Além disso, percebemos que a educação não formal pode, de fato, contribuir com os ideais da Educação em Economia Solidária, como forma de inserir socialmente aqueles que foram excluídos pela educação formal fornecida pela escola.
About three cases in mathematics education for solidarity economy enterprises
Sobre tres casos en educación matemática par empreendimientos de economía solidaria
Keywords: Ethnomathematics; Solidarity economy; Educational processes in mathematics education; Non-formal education; Etnomatemática; Economía solidaria; Procesos educativos en educación matemática; La educación no formal; Etnomatemática; Economia solidária; Processos educativos em educação matemática; Educação não formal